Reconceptualizing the Intellectual Revolution: A Comparative Study of Thales and Muhammad - Cecep Sumarna; Pendi Hasibuan; Heri Gunawan; Fuad Hilmi; Abdulghani Tehmamad (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This research explores the fundamental epistemological transformation in human consciousness from the dominance of mythos to the emergence of logos through a comparative study of two transformational figures: Thales of Miletus and the Prophet Muhammad (peace be upon him). This research aims to analyze the mechanism of the intellectual revolution initiated by the two figures, compare their models of thought, and examine their impact on civilization. Using a qualitative-comparative approach within the framework of comparative intellectual history, historical philosophy, and hermeneutics, this study analyzes primary and secondary sources to reconstruct these epistemological shifts. The results of the study show that although both figures managed to transition their societies towards argumentative and systematic reasoning, they followed different trajectories. Thales pioneered the rational-naturalistic paradigm by desacralizing the cosmos and seeking material principles (arche). At the same time, Muhammad initiated the rational-transcendental paradigm by integrating revelation, reason, and ethics into a monotheistic epistemology. The main difference lies in the source of its epistemological legitimacy: one is rooted in autonomous human observation and the other in prophetic rationality. This article offers a cross-civilizational approach to intellectual history and provides a new perspective on the plurality of human rationality. Finally, this research proposes a synthesis of civilization that bridges the gap between rationality and spirituality, offering an alternative framework for addressing the modern epistemological crisis through an inclusive, non-Eurocentric dialogue.